運動機能評価のための立ち上がり動作のビデオ解析 - 植松, 智子; 後藤, 寛司; 木山, 幸子; 植田, 和也; 中井, 敏晴; 國見, 充展; 冨田, 秀仁; 金井, 章; 田中, あゆ子 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
Loss of muscular strength and decline of balance in older adults impairs their ability to perform activities of daily living, such as walking or moving from a sitting to a standing position (sit-to-stand). To develop care methods to maintain their quality of life, it would be useful to evaluate the changes in their movement characteristics using conventional techniques. We investigated the potential of video analysis of the sit-to-stand motion in several applications, i.e., hemiplegia, a rucksack carrying model and physical battery, in older adults. As a result, the sit-to-stand motion reflected the changes in motor function due to muscle weakness and paralysis. Motion analysis using the sit-to-stand motion could be suitable for evaluating the physical abilities of older adults. We review these examples and discuss the research direction of video analysis for both the diagnosis of motor function, as well as supporting health promotion activities.